2008
DOI: 10.1080/17486020802220587
|View full text |Cite
|
Sign up to set email alerts
|

Stability of highway embankments constructed on sloping ground against translational failure

Abstract: A translational failure of a highway embankment constructed on sloping ground may occur either in the mode of overall instability or in the mode of local instability. The stability analysis of the first mode is based on the assumption that the whole cross-section of the embankment will slide along the inclined base surface, whilst the second mode is based on the assumption of Rankine's active state of stress. In this paper the determination of the prevalent mode of failure --overall or local --is provided via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The last remain stable at the angle of rest of its material. In addition, the loss wedge to the upslope of the respective active is the one that determines the amplitude of failure at Pantelidis (2008a) the Rankine's active failure plane passes very close or through the intersection point between the crest and the outer slope of the embankment (Figure 1). Based on the above-mentioned failure pattern, a semi-analytical model for the determination of the vertical deformation of non-cohesive, homogeneous road embankments founded on sloping ground without benches has been developed.…”
Section: Notation Amentioning
confidence: 99%
See 1 more Smart Citation
“…The last remain stable at the angle of rest of its material. In addition, the loss wedge to the upslope of the respective active is the one that determines the amplitude of failure at Pantelidis (2008a) the Rankine's active failure plane passes very close or through the intersection point between the crest and the outer slope of the embankment (Figure 1). Based on the above-mentioned failure pattern, a semi-analytical model for the determination of the vertical deformation of non-cohesive, homogeneous road embankments founded on sloping ground without benches has been developed.…”
Section: Notation Amentioning
confidence: 99%
“…Introduction Pantelidis (2008a) showed that a non-cohesive highway embankment founded on sloping ground is more prone to fail locally than its whole cross-section to slide downwards. The cross-section of an embankment of this kind can be divided into four areas, the downslope, active and loss wedge and the stable mass.…”
Section: Notation Amentioning
confidence: 99%